DISPERSION OF TITANIUM (IV) OXIDE NANOPARTICLES IN MIXED MATRIX MEMBRANE USING POLYHEDRAL OLIGOMERIC SILSESQUIOXANE FOR CO2/CH4 SEPARATION - TAN YING , GRACE EN (2020)
Titanium (IV) oxide nanoparticles are widely used as inorganic fillers in mixed matrix membranes (MMMs) as they have high adsorption affinity towards CO2 gas. However, TiO2 has a high agglomeration tendency due to its high surface energy, resulting in the formation of TiO2 clusters which will deteriorate the gas separation performance. Moreover, limited quantitative analyses were conducted to study the filler particles’ dispersion and distribution in MMMs. The correlation of nanoparticles’ dispersion state and gas separation performance was also unclear.